2021
DOI: 10.3389/fnins.2021.732213
|View full text |Cite
|
Sign up to set email alerts
|

Refractory and Super-Refractory Status Epilepticus in Nerve Agent-Poisoned Rats Following Application of Standard Clinical Treatment Guidelines

Abstract: Nerve agents (NAs) induce a severe cholinergic crisis that can lead to status epilepticus (SE). Current guidelines for treatment of NA-induced SE only include prehospital benzodiazepines, which may not fully resolve this life-threatening condition. This study examined the efficacy of general clinical protocols for treatment of SE in the specific context of NA poisoning in adult male rats. Treatment with both intramuscular and intravenous benzodiazepines was entirely insufficient to control SE. Second line inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Nerve agents cause a severe cholinergic crisis that can induce RSE. In animal studies, nerve agents and OPNA intoxication with pesticides have been shown to elicit benzodiazepine RSE ( Morgan et al, 2021 ; Reddy et al, 2021 ). Second-line ASMs were not able to terminate such SE, and no current drug therapy is effective against RSE and SRSE.…”
Section: Benzodiazepine-resistant Status Epilepticus and Its Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Nerve agents cause a severe cholinergic crisis that can induce RSE. In animal studies, nerve agents and OPNA intoxication with pesticides have been shown to elicit benzodiazepine RSE ( Morgan et al, 2021 ; Reddy et al, 2021 ). Second-line ASMs were not able to terminate such SE, and no current drug therapy is effective against RSE and SRSE.…”
Section: Benzodiazepine-resistant Status Epilepticus and Its Managementmentioning
confidence: 99%
“…With the exception of PB, there is no record of the FDA approving an MC via the Animal Rule pathway, which is a very complex and nearly implausible regulatory strategy for new nerve agent MCs. Nerve agent–induced RSE is very resistant to current and new anticonvulsants as seen in experimental rodent model outcomes showing minimal responses to second-line antiseizure medications such as valproate, levetiracetam, and phenytoin ( Morgan et al, 2021 ). There may be a disparity between the PK results of medications in animal RSE models and those in patients with RSE, which may appear as poor efficacy or suboptimal protection if the PK-PD relationship is not clear.…”
Section: Medical Gaps and Challenges In Developing Anticonvulsants Fo...mentioning
confidence: 99%
See 1 more Smart Citation